Adaptive social protection: a persistent illusion or the way forward for climate adaptation and social inclusion? - Desai, Bina; Meddings, George; Campbell, Raramai; Läderach, Peter R.D. (2023)
The concept of adaptive social protection has evolved over the past two decades, and examples of practice point to significant potential for accelerating the interconnection between social protection mechanisms and climate-smart practices and adaption. However, there is a lack of evidence on how actual practices can and should change, and on resilience outcomes. This policy brief is based on a study undertaken by the CGIAR FOCUS Climate Security team of the Alliance of Bioversity International and CIAT within the CGIAR initiative on Gender Equality (HER+), comprising of a global review of recent progress in concepts, policies and practices, and three deep dives into social protection landscapes and programmes in India, Jordan and the Sahel region.